PENETAPAN ASAL USUL ANAK HASIL POLIGAMI DI BAWAH TANGAN PERSPEKTIF MAQASID SYARIAH (Studi Terhadap Penetapan Pengadilan Agama Sibuhuan Nomor: 81/Pdt.G/2020/PA.Sbh) - Mala, Revita; Harahap, Ikhwanuddin; Halomoan Hsb, Putra (USRAH: Jurnal Hukum Keluarga Islam, 2025)
Determination of the origin of children plays a very significant role in family law, especially from the perspective of Islamic law which emphasizes the importance of protecting children's rights. The main focus of this study is the Determination of the Sibuhuan Religious Court with Number: 81/Pdt.G/2020/PA.Sbh which is analyzed through the maqasid sharia approach according to Jasser Auda's thinking. This study uses a library research method with a normative approach. The results of the study show that the judge's considerations in the decision cover three main aspects. From a legal perspective, the judge adheres to the applicable legal provisions. From a philosophical perspective, the importance of maintaining harmony in the family structure of Indonesian society is considered. Meanwhile, sociologically, this decision also takes into account the norms that live in society, the need for legal certainty, and efforts to reduce social stigma against children. Analysis based on Jasser Auda's maqasid sharia version shows that the decision reflects the application of six interconnected maqasid elements. First, the application of the al-idrakiyah principle (cognitive), which shows legal awareness of children's rights. Second, al-kulliyyah (comprehensiveness), which is a comprehensive consideration of all aspects of a child's life. Third, al-infitahiyyah (openness), which is the courage to adapt the law to the social context. Fourth, al-harakiyyah (dynamic hierarchical structure), which is seeing the relationship between legal principles. Fifth, ta'addud al-ab'ad (multidisciplinary dimension), which is the integration between law, social, culture, and religion. Finally, the principle of al-maqasidiyyah (goal orientation), which is ensuring that the decisions taken are truly directed towards the welfare of the child as a whole.